2015
DOI: 10.9788/tp2015.3-12
|View full text |Cite
|
Sign up to set email alerts
|

Família e orientação sexual: dificuldades na aceitação da homossexualidade masculina

Abstract: ResumoO presente trabalho teve como objetivo compreender a vivência de homens com orientação homossexual e a construção dos signifi cados da homossexualidade em suas respectivas famílias de origem, por meio das narrativas dos participantes. Participaram cinco pessoas do sexo masculino com orientação homossexual, residentes e domiciliados no interior do Estado de São Paulo, Brasil, que responderam a uma entrevista semi-estruturada e a perguntas para a construção de Genogramas. As narrativas foram compreendidas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
16

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 4 publications
0
6
0
16
Order By: Relevance
“…The main aims of the articles were to investigate the repercussions of homosexuality in the lives of gays and lesbians (Ceballos-Fernández, 2014;Silva, Frutuoso, Feijó, Valerio, & Chaves, 2015), to comprehend the family dynamics during the coming out process (Palma & Levandowski, 2008;Santos, Brochado, & Moscheta, 2007) and to investigate the prejudices faced by homosexuals inside and outside the family context (Santos & Fernandes, 2009;Toledo & Teixeira, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main aims of the articles were to investigate the repercussions of homosexuality in the lives of gays and lesbians (Ceballos-Fernández, 2014;Silva, Frutuoso, Feijó, Valerio, & Chaves, 2015), to comprehend the family dynamics during the coming out process (Palma & Levandowski, 2008;Santos, Brochado, & Moscheta, 2007) and to investigate the prejudices faced by homosexuals inside and outside the family context (Santos & Fernandes, 2009;Toledo & Teixeira, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the families that received this type of support were able to cope better with the changes in the family environment (Etengoff & Daiute, 2013;Puckett, Woodward, Mereish, & Pantalone, 2015). In families that are more adaptable the disclosure is more relaxed, with a greater possibility of acceptance (Robinson & Brewster, 2016;Silva et al, 2015;Willoughby, Malik, & Lindahl, 2006).…”
Section: Trends Psycholmentioning
confidence: 99%
“…Os principais objetivos dos artigos foram investigar as repercussões da homossexualidade na vida de gays e lésbicas (Ceballos-Fernández, 2014;Silva, Frutuoso, Feijó, Valerio, & Chaves, 2015), compreender a dinâmica familiar duran-te o processo de coming out (Palma & Levandowski, 2008;Santos, Brochado, & Moscheta, 2007) e também os preconceitos enfrentados pelos homossexuais dentro e fora do contexto familiar (Santos & Fernandes, 2009;Toledo & Teixeira, 2013).…”
Section: Resultsunclassified
“…Nota-se que as famílias que receberam este tipo de apoio conseguiram lidar melhor com as mudanças no ambiente familiar (Etengoff & Daiute, 2013;Puckett, Woodward, Mereish, & Pantalone, 2015). Em famílias mais adaptáveis a revelação é mais tranquila, com maior possibilidade de acolhimento (Robinson & Brewster, 2016;Silva et al, 2015;Willoughby, Malik, & Lindahl, 2006).…”
Section: A Família Diante Do Processo De Coming Out Do(a) Filho(a)unclassified
“…It is necessary to widen the focus of the vision, to understand same-sex relationships, and to re-signify possible family conflicts and difficulties regarding the acceptance of their sexual orientation. 16 Studies have shown that the timing of the disclosure of same-sex relationships to other people depends on the current circumstances of the homosexual person's life, the social environment, or the personal value given to revelation. When dealing specifically with the family, this disclosure has exclusive considerations related to individual and family characteristics.…”
Section: Discussionmentioning
confidence: 99%